The impact of humanising hospital care on health outcomes: an observational study protocol - Regina Allande-Cussó; Yolanda-Angustias Mejías-Martín; María-Dolores Quiñoz-Gallardo; Ana-María Porcel-Gálvez (BMC Nursing)
Abstract Background The humanisation of care has emerged as a crucial element in contemporary healthcare, with several countries adopting the concept of patient and family-centred care. This change signifies an ongoing evolution within contemporary healthcare, emphasising person-centred approaches, patient autonomy and preferences. The humanisation of care extends beyond patients to include their families and healthcare professionals, to enhance health outcomes, clinical safety, accessibility and therapeutic relationships holistically. This project aims to evaluate the humanisation of care in hospital settings in southern Spain, examining its impact on health outcomes and identifying areas for improvement. Methods The research employs a three-year multiphase approach, combining cross-sectional designs, qualitative-quantitative analyses and psychometric assessments. The study involves a diverse sample population, including patients admitted to several hospitals in southern Spain along with nursing professionals. Data collection incorporates a range of validated tools, items developed ad hoc and sociodemographic variables. Discussion The study findings are expected to offer insight into healthcare management, clinical practice and education. Humanising care has the potential to positively impact health outcomes, and the study methodology may serve as a model for future research and educational programmes in healthcare. Whilst acknowledging its limitations, the study represents a critical step in evaluating the humanisation of care in Spanish hospitals and informing strategies for improvement. In conclusion, this comprehensive study addresses the humanisation of care in hospital settings, examining its dimensions and potential impact on health outcomes. The findings may influence policy decisions, emphasising the need to enhance the humanisation of care as a fundamental aspect of healthcare management. Trial registration NCT06174844 (18/12/2023).